Precise Species Identification and Taxonomy Update for the Genus Kluyvera With Reporting Kluyvera sichuanensis sp. nov. - Liu, Lina; Feng, Yu; Wei, Li; Qiao, Fu; Zong, Zhiyong (Frontiers in Microbiology, 2020)
Kluyvera is a genus within the family Enterobacteriaceae and can cause various human infections but remains poorly studied. A carbapenem-resistant blaNDM-1-carrying Kluyvera strain 090646T was isolated from a hospital sink in Chengdu, China. Whole genome sequencing of the strain revealed that it had 28.2% to 42.3% in silico DNA-DNA hybridization (isDDH) scores and 84.15% to 90.10% average nucleotide identity (ANI) values with other Kluyvera species. Both values are well below the ≥ 70.0% isDDH and ≥ 95-96% ANI cutoffs to define bacterial species, suggesting that the strain represents a novel species of the genus Kluyvera, for which the name Kluyvera sichuanensis. nov. is proposed. Type strain of K. sichuanensis is 090646T (= GDMCC 1.1872T = KCTC 82166T). Strain 090646T can be differentiated from other Kluyvera species by its ability to utilize D-sorbitol but not β-galactosidase (ONPG), D-mannose, glycerin, raffinose, nor sucrose. There were 47 genome sequences labelled as Kluyvera in GenBank, which were curated for precise species identification. Only 33 of the 47 genomes were indeed of Kluyvera and four novel Kluyvera genomospecies were identified, highlighting that the species assignation of bacterial genomes in GenBank need to be curated. Genome sequencing for more strains is required to understand the genus Kluyvera.